Pemahaman Konseptual Dalam Kurikulum Merdeka : Dalam Tinjauan Evaluasi Pendidikan Sains - Naintyn Novitasari; Syukri Hamzah; Rendy Wikrama Wardana (Cv. Digital Education Nusantara, 2026)
The purpose of this article is to synthesize conceptual understanding in the independent curriculum in terms of science education evaluation. Implementation of the Independent Curriculum focuses on acquiring contextual knowledge in each field and environment. The curriculum seeks to develop students' evaluation skills in three areas: attitudes, technical skills, and scientific knowledge. It is based on two layers of competencies: core and basic competencies. Core Competencies in the Merdeka Curriculum represent the level of ability to achieve graduate competency standards for a student at each grade level. There are four mandatory core competencies for all levels of education and all subjects including science, spiritual ones, social competencies, knowledge and skills. In terms of knowledge competency, conceptual understanding is an inseparable part of science concepts because conceptual understanding is a basic competency in science learning. This competency is part of the science graduation standards listed in Ministry of Education and Culture article number 20 of 2016. Therefore, students need conceptual understanding to learn science successfully.